Analisis Pengenalan Literasi Digital pada Anak Usia Dini di Era Abad 21: Analysis of Introduction to Digital Literacy in Early Childhood in the 21st Century - Sarifah Hairani; Irena Yolanita Maureen; Nurul Khotimah (Universitas Ngudi Waluyo, 2025)
Educational applications and technology are developing rapidly to meet the needs of the times. To remain relevant in the modern era, expertise in innovation, digital literacy and learning is required (Adiarsi et al., 2015). According to the Ministry of Education and Culture (2017), digital literacy, especially in early childhood, is an important life skill in the era of modern technology. This research reveals the introduction of digital literacy in early childhood and how it is related to facing technological challenges in the future. The aim of this research is to analyze literature regarding the introduction of digital literacy in early childhood in the modern era. This research will focus on the benefits and problems of using devices, the role of parents, components of introducing digital literacy, learning in schools, and the use of digital literacy tools. Data is collected from primary, secondary and tertiary sources, such as reference books, internet articles, journals and related research; Qualitative literature studies use content analysis methods to test relevant concepts and theories. The research results support the importance of digital literacy in early childhood. If used correctly, use of the device can have a positive impact. Digital literacy, which involves various aspects and approaches to learning, is influenced by parental understanding and is an important skill. Literacy education and